2005
DOI: 10.1007/s10709-005-0368-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cytogenetic Analysis between the Grasshopper Species Chromacris nuptialis and C. speciosa (Romaleidae): Constitutive Heterochromatin Variability and rDNA Sites

Abstract: The chromosomes of Chromacris nuptialis and C. speciosa were comparatively analyzed using different cytogenetic techniques, in order to determine the level of karyotypic similarities and differences between the species. The results show similarities in chromosome number (2n=23,X0) and acrocentric morphology. In some C. nuptialis individuals meiotic irregularities were detected involving the L(2) bivalent. This bivalent was delayed and presented anaphasic bridges and other aberrations. Differences in constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…Data may be most plentiful for the Acrididae family [10,15,16,24]. The 18S rDNA clusters are restricted to a single medium-sized autosomal pair in C. nuptialis , C. speciosa , and X. robustus , corroborating previous studies from Loreto et al [23] and Souza et al [22], which suggests that it may be the ancestral bearer of 18S rDNA. This hypothesis is supported by the data from X. d. angulatus, another Romaleidae grasshopper, which showed the 18S rDNA gene in a medium-sized pair [21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Data may be most plentiful for the Acrididae family [10,15,16,24]. The 18S rDNA clusters are restricted to a single medium-sized autosomal pair in C. nuptialis , C. speciosa , and X. robustus , corroborating previous studies from Loreto et al [23] and Souza et al [22], which suggests that it may be the ancestral bearer of 18S rDNA. This hypothesis is supported by the data from X. d. angulatus, another Romaleidae grasshopper, which showed the 18S rDNA gene in a medium-sized pair [21].…”
Section: Discussionsupporting
confidence: 83%
“…In grasshoppers, the rDNA is sometimes located in constitutive heterochromatin (CH) regions, so a possible rDNA spread mechanism may be associated with CH spread. Previous studies have reported an amplification and dispersion of CH in eight species from six genera ( Brasilacris , Chromacris , Phaeoparia , Radacridium , Xestotrachelus , and Xyleus ) from the Romaleidae family [21,23,25-27]. On the other hand, when data from the 10 ribosomal sites found in B. gigas , C. nuptialis , C. speciosa , and X. robustus are correlated with information from previous studies [22,25] related to the CH pattern, the results indicate four ribosomal sites in CH regions and six ribosomal sites outside CH regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These karyotypes are similar to those reported for most species of Romaleidae (Mesa et al 1982, Souza and Kido 1995, Loreto et al 2005). However, in Xestotrachelus robustus (Bruner, 1911), pairs S 9 and S 10 are meta- or submetacentric and originated by pericentric inversion.…”
Section: Discussionsupporting
confidence: 89%
“…There are three patterns of distribution of GC-rich blocks in grasshoppers: (i) CMA 3 + bands related to NORs location (Souza et al 1998, Loreto and Souza 2000, Rocha et al 2012); (ii) CMA 3 + in all chromosomes (Souza et al 1998, Pereira and Souza 2000); and, (iii) GC-rich blocks in some chromosomes (Loreto and Souza 2000, Souza et al 2003, Loreto et al 2005, Souza and Melo 2007, Rocha et al 2012). AT-rich heterochromatin is rarely encountered in Acrididae, as is the case Arcyptera fusca (Pallas, 1773), A. tornosi Bolívar, 1884 (Bella and Gosálvez 1991) and Dociostaurus genei (Ocskay, 1832) (Rodríguez Iñigo et al 1993).…”
Section: Resultsmentioning
confidence: 99%